Upaya Meningkatkan Omzet Penjualan Pada Usaha Mikro Kue Tradisional “Laris“ Di Menur Pumpungan Kota Surabaya - Kunto Inggit Gunawan; Mataji Mataji; Sigit Santoso (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
Since the implementation of the ASEAN Economic Community (AEC) at the end of 2015, it should encourage all economic actors, including SMEs and Micro Enterprises, to improve themselves in order to improve the quality of production of both goods and services. If this is not done, then Indonesia will be an